Smoking and Risk Factors in Deep Vein Thrombosis - Prescott, R J; Jones, D R B; Vasilescu, C; Henderson, J T; Ruckley, C V (Thrombosis and Haemostasis, 1978)
The incidence of deep vein thrombosis (DVT) as diagnosed by the 125I fibrinogen test (125IFT) was determined in a series of 300 newly admitted medical and 201 surgical patients. 6 medical patients died before 125IFT screening could be completed. The incidence of DVT was l4% in medical patients and 18% in surgical patients. Increasing age, a malignant condition and a past history of thromboembolism all increased the risk of DVT. Increasing levels of cigarette smoking were found to be associated with a reduced incidence of DVT. Although statistical significance was achieved at only the 10% level for this finding it is in agreement with the results from studies on patients with myocardial infarction. The protective effect of cigarette smoking was observed at all ages, and in both medical and surgical patients.